2015
DOI: 10.17957/ijab/14.0009
|View full text |Cite
|
Sign up to set email alerts
|

Control of Earias vittella (Lepidoptera: Noctuidae) by Beauveria bassiana along with Bacillus thuringiensis

Abstract: A laboratory strain of Beauveria bassiana sensu lato (Balsamo) Vuillemin (Hypocreales: Clavicipitaceae) and commercial formulation of Bacillus thuringiensis (Berliner) were assessed against three field populations of Earias vittella F. ) were applied alone and in combination against 2 nd and 4 th larval instars. The mortality was observed until pupation. The bioassays were carried out at 25°C and 75% RH The highest larval mortality was observed in the population from Faisalabad with lowest pupation rate, adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…E. vittella has developed resistance against insecticides that are used to control them and to overcome this problem researchers has to concentrate on biological means like microbial agents for development of biopesticides for control of insect pests [19] . Biocontrol efficiency of Bt in combination with Beauvaria bassiana against larvae of Earias vittella and recorded 100% mortality when treated with Bt and B. bassiana in the combination of 0.5µg /g and 1.58x10 8 conidia / ml, respectively [20] . Pazhanisamy and Archunan [21] had used biological extracts like neem leaf extract (NLE) 5%, Prosophis leaf extract 5%, Calotropis leaf extract 5%, Pungam oil 3% Neem seed kernel extract (NSKE) 5% and panchagavya for biocontrol of Earias vittella.…”
Section: Screening Of Insecticidal Activity Of Entomopathogenic Bacteria Against Larvae Of Earias Vittellamentioning
confidence: 99%
“…E. vittella has developed resistance against insecticides that are used to control them and to overcome this problem researchers has to concentrate on biological means like microbial agents for development of biopesticides for control of insect pests [19] . Biocontrol efficiency of Bt in combination with Beauvaria bassiana against larvae of Earias vittella and recorded 100% mortality when treated with Bt and B. bassiana in the combination of 0.5µg /g and 1.58x10 8 conidia / ml, respectively [20] . Pazhanisamy and Archunan [21] had used biological extracts like neem leaf extract (NLE) 5%, Prosophis leaf extract 5%, Calotropis leaf extract 5%, Pungam oil 3% Neem seed kernel extract (NSKE) 5% and panchagavya for biocontrol of Earias vittella.…”
Section: Screening Of Insecticidal Activity Of Entomopathogenic Bacteria Against Larvae Of Earias Vittellamentioning
confidence: 99%
“…These fungal species together with other known hypocrealean fungi, such as I. fumosorosea , M. brunneum , M. robertsii , and Hirsutella thompsonii Fisher, are commonly used against a broad range of arthropod pests ( Dara, 2019b ). They are mostly applied through inundative approaches ( Bamisile et al, 2018b ; Jaber and Araj, 2018 ) and have been reported to be effective against several insects of different feeding guilds including aphids, locusts, thrips ( Gulzar et al, 2021 ), grubs ( Wakil et al, 2017 ; Yasin et al, 2019 ), moths ( Ali et al, 2015 ; Tahir et al, 2019 ), mites, mosquitoes, whiteflies, and tephritid fruit flies ( Dong et al, 2016 ; Bamisile et al, 2020 ; Canassa et al, 2020 ; Usman et al, 2020 ). Additionally, EPF have been found to be pathogenic against phytopathogenic nematodes and other soil-borne pests ( Pocasangre et al, 2000 ).…”
Section: Entomopathogenic Fungi As Alternatives To Chemical Pesticides: a Reality Or Myth?mentioning
confidence: 99%
“…For example, these effects were observed during combined fungal infection (Beauveria, Metarhizium) and bacteriosis (Bacillus thuringiensis, Pseudomonas sp.) on Musca domestica (Mwamburi et al, 2009), Ostrinia furnacalis , Locusta migratoria (Lednev et al, 2008), Helicoverpa armigera (Wakil et al, 2013), Sesamia nonagrioides (Mantzoukas et al, 2013), Earias vittella (Ali et al, 2015), and Leptinotarsa decemlineata (Kryukov et al, 2009;Wraight and Ramos, 2005). The majority of mixed infection studies are related to identifying methods to enhance bioinsecticide efficacy.…”
Section: Introductionmentioning
confidence: 99%